MSPWM Based Implementation of Novel 5-level Inverter with Photovoltaic System - R. Palanisamy; K. Vijayakumar; D. Selvabharathi (Institute of Advanced Engineering and Science, 2017)
This paper proposes a novel 5-level dc-ac converter circuit using with 6 power semiconductor switches. The proposed multilevel inverter generates five-level ac output voltage by implementing Multi-carrier sinusoidal pulse width modulation (MSPWM) technique with reduced number of switches. The voltage stress on each switching devices and common mode voltage can be minimized from the suggested system. The designed system gives better controlled output current and improved output voltage with diminished total Harmonic Distortion value. The operating principles of the proposed inverter are discussed. DC Input for the proposed system is obtained from PV System. Finally, an experimental prototype of the proposed system with 12-V input voltage and 20 V /5 W output is implemented along with simulation output of the waveform to the load. The efficiency and the reduction of harmonic content are discussed.